2021
DOI: 10.3390/rs13081488
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Land Subsidence in the Po River Delta (Northern Italy) Using Geodetic Networks

Abstract: The Po River Delta (PRD, Northern Italy) has been historically affected by land subsidence due to natural processes and human activities, with strong impacts on the stability of the natural ecosystems and significant socio-economic consequences. This paper is aimed to highlight the spatial and temporal evolution of the land subsidence in the PRD area analyzing the geodetic observations acquired in the last decade. The analysis performed using a moving window approach on Continuous Global Navigation Satellite S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 67 publications
2
22
0
Order By: Relevance
“…The most exposed are those of Egypt (12.879 km 2 ), Italy (10.060 km 2 ) and France (3.681 km 2 ). In these countries, the river deltas of Nile (Egypt, about 12.879 km 2 ), Po (Italy, about 4.000 km 2 ) and Rhone (France, about 2.000 km 2 ), which are undergoing high rates of land subsidence due to natural (soil compaction) and anthropogenic (ground fluid exploitation) processes (Syvitski et al 2009, Bohannon 2010, Cenni et al 2021, Pont et al 2002, are at high risk of flooding in 2050-2100-2150, as shown by the revised SL projections show in figure 6 It is worth noting that most of the population living along the coasts of the Mediterranean is not aware of SL rise, land subsidence and related coastal hazard that impact on the environment, coastal infrastructures, and human activities (Loizidou et al 2023). In addition, the current resident population in the Mediterranean countries is about 450 million with a possible rise to 700 million by 2100.…”
Section: Exposed Zonesmentioning
confidence: 99%
“…The most exposed are those of Egypt (12.879 km 2 ), Italy (10.060 km 2 ) and France (3.681 km 2 ). In these countries, the river deltas of Nile (Egypt, about 12.879 km 2 ), Po (Italy, about 4.000 km 2 ) and Rhone (France, about 2.000 km 2 ), which are undergoing high rates of land subsidence due to natural (soil compaction) and anthropogenic (ground fluid exploitation) processes (Syvitski et al 2009, Bohannon 2010, Cenni et al 2021, Pont et al 2002, are at high risk of flooding in 2050-2100-2150, as shown by the revised SL projections show in figure 6 It is worth noting that most of the population living along the coasts of the Mediterranean is not aware of SL rise, land subsidence and related coastal hazard that impact on the environment, coastal infrastructures, and human activities (Loizidou et al 2023). In addition, the current resident population in the Mediterranean countries is about 450 million with a possible rise to 700 million by 2100.…”
Section: Exposed Zonesmentioning
confidence: 99%
“…Cenni et al [22] highlighted the spatial and temporal evolution of the land subsidence in the Po River Delta (PRD) area (Italy) analyzing time-series obtained from CGNSS stations using a moving window approach temporally overlapping with both the surveys of a new GNSS network (PODELNET-PO DELta NETwork) (46 non-permanent sites measured in 2016 and 2018), and InSAR data (SBAS processing of Sentinel-1A/B images from 2014 to 2017). The authors investigated the integration between these data: since the InSAR technology does not perform well in high vegetated areas or areas with high temporal variability, the PODELNET sites represent an important improvement for the monitoring of the land subsidence in the PRD.…”
Section: Overview Of Contributionsmentioning
confidence: 99%
“…Due to the increased concern, many recent scientific articles addressing this subject have been published in recent years. Studies include those from Australia [10], France [11], Italy [12], Poland [13], Turkey [14], USA [15], Mexico [16], Argentina [17], Japan [18], China [3,19], Thailand [20], Indonesia [21], India [22], and Iran [23,24]. A repeating message from these investigations is that due to the extensive distribution of LS and its potentially devastating consequences for the economy and environment, there is an urgent need for LS sensitivity assessments, LS sensitivity zone assessments, and identification of the leading causes of LS.…”
Section: Introductionmentioning
confidence: 99%